(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The expansion of the 2nd Level Federal Court, either by increasing the number of its members or by creating new Federal Regional Courts, represents the possibility of responding to society’s desire for a more accessible, swift and efficient justice system. The popular outcry against corruption and impunity, which have unfortunately gone hand in hand, needs an effective response from the powers that be.